CRISIS MANAGEMENT STRATEGIES IN THE HOSPITALITY SECTOR: A CASE OF TÜRKİYE (Third Sector Social Economic Review, 2023)
The tourism sector plays a vital role in enhancing the economies of nations by creating jobs, attracting foreign travellers and increasing total income. However, the sector is vulnerable to crises such as conflicts, terrorism, natural disasters, and other unfavourable events. This research focused on hotel managers in Türkiye working in hotels that are classified by the Ministry of Culture and Tourism as 1-, 2-, 3-, 4-, or 5-star hotels and hold either a tourism operating certificate or a tourism investment certificate. The study was undertaken by collecting data from the managers of hotels in different cities of Türkiye, such as Ankara, Antalya, Istanbul, Izmir and Nevsehir. The primary data were collected from 415 hotel managers or owners.In this study, the impact of pre-crisis measures on the crisis forecasting and crisis management process is evaluated, and the outcomes of the crisis forecasting and management process in the Turkish hospitality sector are examined. The most recent crisis for the Turkish hospitality industry is considered as the COVID-19 crisis. The impact of the COVID-19 crisis and other crises on Turkish tourism and the approaches of hotel managers before, during and after the pandemic were analysed. Hotel managers' perspectives on the impact of the COVID-19 pandemic on the Turkish tourism sector and the strategies implemented against the effects of the pandemic were evaluated. In terms of preparation and planning for possible crises, it was observed that a significant number of hotels exhibited a high level of effectiveness and preparedness in controlling and mitigating the crisis. Action plans developed and implemented in sales, marketing fields and savings measures to prevent potential crises.
Keywords: Hospitality Sector; Crisis Management; Tourism; Management; COVID-19 Pandemics